Fresh ideas for preserving fish - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1988)
Scientists in the south of India are experimenting with a plastic pouch that could one day replace canning as a means of preserving fish, especially sardines. The pouch was invented in the USA and already is in common use in Japan. It consists of...